Drawing the places through street art. The case study of Furore “painted village” - Nicola Pisacane (Disegnare con, 2020)
The abstract introduces a research and census activity carried out at the municipality of Furore in the Amalfi Coast (Italy), located in the bound-ary of the site registered in the WHL of Unesco. The urban landscape of the small coastal center is characterized by colorful paintings and murals that we can find on many houses. Aim of the article is to introduce the collection of census data that has been merged into a GIS that not only identifies the geographical location of each work but analyses its technique (painting, ceramic, metallic), size, author, as well as the object of the depiction, very often related to glimpses of the territory or to moments of local life. The tradition of murals in the municipality of Furore can be traced back to 1982, the year from which Italian and foreign artists dedicated to the art of wall drawings have succeeded, making the small town one of the main and most original painted village of the peninsula, listed in the Italian Association of Painted Villages. The survey methodology started from the establishment of a census sheet, support for the sur-vey in the field of the heritage of murals of the municipality of Furore. The census was carried out using open source software and apps for localization and information acquisition. Known the heritage of works present on the municipal territory, the research continued with the analysis of the most significant murals representing urban scenes and the articulated orography of the places, simulating on the piano support of the representation spaces through pseudo perspectives. Results are all catalogued and interrogated in the digital platform that wants to be a searchable and questionable tool as well as providing a wealth of information that can be useful for conservation that in the future the murals will require. DOI: https://doi.org/10.20365/disegnarecon.24.2020.22